What Gets Measured, Gets Done: Understanding and Addressing Middle‐Class Challenges. (8th July 2019) - Ely, Todd L.; Propheter, Geoffrey; Jones, Rich; Wasserman, Scott
Abstract: Middle‐class families face a range of challenges, including uneven income growth, imposing child care costs, and affordability gaps for higher education. The ideal policies by which policy makers and public administrators can aid the middle class are far from obvious. Policy solutions are likely to mirror our government and population, meaning that they will be decentralized and varied. Achieving a "growing and thriving middle class" requires understanding the composition of the middle class across the country. Benchmarking and measuring the middle‐class condition at the state and substate levels is critical to crafting and adopting effective policy solutions. This Viewpoint essay highlights the Colorado context to demonstrate the measurement of the middle class and tracking of its lived experiences .